The Politics of Symbolic Laws: State Resistance to the Allure of Sex Offender Residence Restrictions. (28th August 2020) - Williams, Monica; Comartin, Erin B.; Lytle, Robert D.
Abstract : Sex offender residence restrictions are largely symbolic laws that address constituent demands to do something about sex crimes without actually reducing sex offenses. While the majority of US states have implemented such restrictions, this exploratory study examines three states that have resisted the allure of these symbolic laws. Using data from state government archives, we analyze expressive and instrumental rationales for rejecting residence restrictions to explore what facilitates the failure of a symbolic law. We find that while supporters and opponents both made largely instrumental arguments, opponents framed their instrumental arguments in expressive terms. Legislators' policy positions, reliance on empirical evidence, and testimony from bureaucrats also contributed to the failure of residence restrictions in these states. Our findings help explain why empirically ineffective sex offender laws appeal to the public and politicians, how these laws might be scaled back, and how symbolic laws may lose their power in some contexts.